Integrating I-DEVS and schedulability methods for analyzing real-time systems constraints. (December 2022) - Mello, Braulio A; Wainer, Gabriel A
The design of embedded real-time systems (RTS) is challenging due to the criticality of the timing constraints of these systems. Various informal and formal methods for RTS design have been proposed, both in the design space and the real-time execution at the hardware level, but many of these methods are not effective when the complexity of the system scales up. Here, we discuss a new method to integrate a modeling (and simulation) formalism that allows designing complex systems specifications for real-time constraints called Imprecise-DEVS (I-DEVS), and the mapping of such high-level models into a real-time task model. This method allows analyzing real-time constraints both at the high level of modeling as well as the low level of the tasks executed by the processing units and the Operating System. A new method to study the schedulability of the task models is proposed. The method provides a design analysis space from the model level, up to the individual tasks, with a focus on the schedulability of real-time constraints under transient overloading conditions.